Algorithm of Computer Model Realization of Ferroresonance Overvoltages and Their Suppression at Asymmetric Regimes of Power Transmission Lines - E. V. Dmitriyev; A. M. Gashimov; I. R. Pivchik; A. R. Babayeva (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper contains results of investigations pertaining to ferroresonance currents. These investigations have been carried out by means of computer modeling of incomplete-phase regime of PTL with the purpose to select criteria for starting devices which are applied for detection and suppression of ferroresonance processes. The considered device is designed to switch off PTL with idle power transformer at incomplete phase regime. Recommendations for realization of the proposed model have been formulated and expediency concerning combination of insulation protection of network equipment and overvoltage limiter against ferroresonance overvoltages in a single algorithm has been shown in the paper.